Case Report: Anomalous origin of the left main coronary artery arising from the left ventricular outflow tract - Thuy, Huynh Thi Minh; Luan, Tran Minh Bao; Anh, Pham Tho Tuan; Dinh, Nguyen Hoang (Frontiers in Cardiovascular Medicine, 2025)
An anomalous origin of the left main coronary artery arising from the left ventricular outflow tract is an exceedingly rare congenital coronary anomaly, typically associated with impaired myocardial perfusion. Here, we report the case of a 67-year-old asymptomatic woman in whom an anomalous origin of the left main coronary artery, arising from the left ventricular outflow tract below the aortic valve, was incidentally identified during routine preoperative cardiac evaluation. Despite the anatomical abnormality, the patient exhibited no clinical or imaging evidence of myocardial ischemia. This finding is likely explained by a marked dilation of the right coronary artery and the presence of well-developed collateral circulation supplying the left coronary system. With no evidence of ischemia and maintained ventricular function, a non-interventional approach was deemed appropriate. This case highlights the importance of comprehensive anatomical and functional assessment in detecting clinically silent coronary anomalies and underscores the value of advanced cardiac imaging in the preoperative evaluation of elderly patients undergoing non-cardiac procedures.